Gastric Adenocarcinoma of the Fundic Gland Type Treated by Endoscopic Mucosal Resection: A Case Report and Review of the Literature - Eleanor Lewin; Philip Daroca; Sanjay Sikka; Tong Wu; Yukihiro Nakanishi (Case Reports in Pathology)
Gastric adenocarcinoma of the fundic gland type (GA-FG) is a rare entity that has only recently been described and defined. There is ongoing controversy regarding the malignant potential of this lesion. We report the case of a GA-FG in a 49-year-old Caucasian man who was referred to endoscopy for management of an incidentally found gastric polyp. Endoscopy showed a single polypoid lesion in the gastric fundus which was successfully removed with endoscopic resection. Grossly, the polyp measured 1.1 cm in greatest dimension. Microscopic examination showed irregularly branched neoplastic glands covered with a nonneoplastic foveolar epithelium. The continuity between the neoplastic glands and the fundic glands is clearly identified, indicating the tumor arose from the fundic glands. The tumor cells exhibited occasional oxyntic cytoplasm with enlarged atypical nuclei. The tumor invaded the submucosa with complete disruption of the muscularis mucosae and mild lymphocytic and fibroblastic stromal reaction. No necrosis, mitosis, or lymph-vascular invasion was identified. Although some authors have proposed reclassification of GA-FGs as oxyntic gland polyps/adenomas, in light of several reported cases with submucosal invasion as well as lymphatic invasion, we maintain that this neoplasm is best categorized as an extremely well-differentiated adenocarcinoma to reflect its invasive potential.